The Development of Criminal Law in the Context of Human Rights Protection: Analysis and Implementation (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research examines the evolution of criminal law in Indonesia with specific focus on its relationship with human rights protection frameworks. The study employs qualitative research methodology to analyze how criminal law reforms have incorporated human rights principles, particularly in the context of the new Criminal Code (Law Number 1 of 2023). Through comprehensive document analysis and normative juridical approach, this research identifies key developments, challenges, and implementation gaps in Indonesia's criminal justice system. The findings reveal a significant paradigm shift from colonial-era punitive approaches toward more balanced frameworks that consider human rights protections, though several contradictions and implementation challenges persist. The research concludes that while Indonesia has made substantial progress in harmonizing its criminal law with international human rights standards, further reforms are needed to address remaining inconsistencies and ensure effective implementation of human rights protections within the criminal justice system. This study contributes to the ongoing discourse on balancing state sovereignty with international human rights obligations in criminal law development.